Aortoesophageal Fistula after Endovascular Aortic Aneurysm Repair of a Mycotic Thoracic Aneurysm - Elizabeth Gavens; Zehra Zaidi; Wissam Al-Jundi; Palepu Kumar (International Journal of Vascular Medicine)
Mycotic aneurysms constitute a small proportion of aortic aneurysms. Endovascular repair of mycotic aneurysms has been applied with good short-term and midterm results. However, the uncommon aortoenteric fistula formation remains a potentially fatal complication when repairing such infective aneurysms. We present the case of an 80-year-old woman with thoracic and abdominal aortic mycotic aneurysms, which were successfully treated with endografting. However, the patient presented 3 months later with upper gastrointestinal bleeding secondary to erosion of the thoracic graft into the oesophagus. The patient was treated conservatively due to the high risk of surgical repair. There is currently little exposure to the management of mycotic aortic aneurysms. If suspected, imaging of the entire vasculature will aid initial diagnosis and highlight the extent of the disease process, allowing for efficient management. Aortic endografting for mycotic thoracic aneurysms is a high-risk procedure yet is still an appropriate intervention. Aortoenteric fistulae pose a rare but severe complication of aortic endografting in this setting.